A LINGUISTIC STUDY ON “GET” PHRASAL VERBS IN ENGLISH WITH REFERENCE TO THE VIETNAMESE EQUIVALENTS / Chu Thị Thu Hà; GVHD: Ho Ngoc Trung - Chu, Thị Thu Hà
The aim of this thesis is analyzing the linguistic of ‘get’ phrasal verbs and raising Vietnamese learners’ awareness of these verbs, the use of “get” phrasal verbs has not yet been the specific focus in different researches, so that is why this thesis seeks to make a contribution and help them improve their real world communication exactly and successfully in English. In order to study the subject effectively, a flexible combination of methods is employed. The research is used descriptive method and qualitative to analysis the data The syntactic and semantic feature of ‘get’ phrasal verbs can be found as follows. In term of syntactic, ‘get’ phrasal verbs can have intransitive or transitive features, be separable or inseparable. In term of semantics, ‘get’ phrasal verbs has non-idiomatic, idiomatic meaning as well as metaphoric meanings. As ‘Get’ phrasal verbs have specific semantics features, they normally do not have exactly equivalent translations in Vietnamese, but there can be found some similar expressions in terms of meaning. The results taken from the test conducted at HHT later have been classified to help finding out some possible implications for mastering these typical phrasal verbs